Implications of Labeling the Criminal Armed Group in Papua as a Terrorist Organization - Milda Istiqomah; Heru Kurniawan; Raras Natasya Anindita (Yustisia, 2025)
Conflict and bloodshed continue in Papua, whether by governmental actors or the Criminal Armed Group. The Coordinating Ministry for Politics, Law, and Security declared the KKB in Papua a terrorist organisation in 2021 after classifying it as a separatist organisation. This study aims to look into what it means that the Papuan government called the KKB a "terrorist organisation."  In this article, socio-legal research examines whether labelling the Papuan KKB as a terrorist group is legal and what that means.  It also includes interviews with state security experts and Papua experts.  The study's results showed that labelling the Papuan KKB as a terrorist group could make the security and human rights situation in Papua worse by fostering more violence and separating peace. The government's application of force may prolong the cycle of violence and human rights violations.   The name does not comply with legal standards since it should have been established through a transparent judicial process rather than by the Coordinating Minister for Political, Legal, and Security Affairs.   For sustainable conflict resolution in Papua New Guinea, a technique that incorporates broader participation and is founded on discussion is essential